O "Bing-Bang" de um professor-estagiário de Educação Física - Tiago Miguel Fraga Carquejo (2021)
In the second year referring to the Master of Teaching in Physical Education in Basic and Secondary Education, the professional internship takes place, which is the first barrier that the intern student faces in his professional journey. This document reports the year of internship of a student intern (the author) in the academic year 2020/2021. With the internship I gained multiple knowledge in order to be able to intervene in the best possible way in a training space in a real teaching context, the school, so important for a future Physical Education teacher. With the completion of this curricular internship, I was able to fight the difficulties that arose, constantly adapt to new learning moments, and transmit knowledge to students. Achieving an understanding of how to integrate myself in the teaching-learning process was a difficulty I initially felt, but which I struggled with throughout the school year. Learning how to build essential documents for a Physical Education teacher, how to work them to be effectively practical, knowing how to share knowledge, knowing how to acquire knowledge, were challenges present in this internship, which took place during an intense academic year. Added to the pandemic moment, everything had to be readjusted to the second. The research theme aimed to explore the value of cooperative learning and dialogic feedback in the acquisition of autonomy in tasks by students. The results showed that anatomy is enhanced when working in heterogeneous groups. This report presents, then, my intervention and decisions that led me to choose a certain way of acting over another, to be able to complete the internship year as successfully as possible.